Novel strategy for depolymerization of avermectin fermentation residue to value-added amino acid product - Ma, Chi; Mao, Zhengxin; Liu, Qingfen (Frontiers in Chemistry, 2024)
Avermectin fermentation residue (AFR) is rich in proteins, which can be depolymerized to value-added amino acids for in-plant reuse. The hydrochloric acid (HCl) hydrolysis is performed and investigated under different conditions, including HCl concentration, solid-liquid ratio, temperature, and time. The hydrolysis degree (HD) of 67.7% can be achieved. The empirical correlation of HD is established with a good practicability to control the HD and predict the experimental conditions. Solid-liquid reaction is confirmed to be dominant during the hydrolysis process. There are 17 kinds of amino acids in the hydrolysate, benefiting the reuse. Avermectin is not detected in the hydrolysate and AFR, and the mass of AFR is reduced by 53.8 wt%. This work provides a novel strategy for the environmentally friendly treatment and meanwhile the resource recovery of AFR.